Combining Molecular Weight Fractionation and Metabolomics to Elucidate the Bioactivity of Vegetal Protein Hydrolysates in Tomato Plants - Lucini, Luigi; Miras-Moreno, Begoña; Rouphael, Youssef; Cardarelli, Mariateresa; Colla, Giuseppe (Frontiers in Plant Science, 2020)
Plant-derived protein hydrolysates (PHs) have gained prominence as biostimulants because of their potential to increase productivity, nutrient efficiency and tolerance to abiotic stresses. The comprehension of the bioactive fractions involved in the biostimulant activity of PH is a complex task, but it can also lead to significant improvements in the production of more effective plant biostimulants. The aim of this work is to shed light onto the bioactivity of different PH dialysis fractions (PH1 < 0.5-1 kDa; PH2 > 0.5-1 kDa; PH3 < 8-10 kDa; PH4 > 8-10 kDa) of a commercial PH-based biostimulant through a combined in vivo bioassay and metabolomics approach. Overall, both the PH and its fractions increased the root length of tomato cuttings, compared to control. Moreover, the highest root length was obtained in the treatment PH1 following foliar application. Metabolomics allowed highlighting a response to PH1 that involved changes at phytohormones and secondary metabolite level. Notably, such metabolic reprogramming supported the effect on rooting of tomato cuttings, being shared with the response induced by the positive control indole-3-butyric acid. Taken together, the outcome of in vivo assays and metabolomics suggest an auxin-like activity of the selected PH1 fraction.